Foaming and interfacial properties of desalted duck egg white nanogels after weak enzymatical hydrolyzation. (January 2023) - Zhou, Bin; Zhao, Jingyun; Rong, Yujuan; Li, Mengchen; Liang, Hongshan; Li, Bin; Sun, Jing
Abstract : Gel-assisted desalination is an efficient way of desalting salted duck egg whites, but results in severe loss of egg white functional properties, especially foaming properties. Here, slightly enzymatical hydrolyzation was used as a promising method to improve the interfacial properties of desalted duck egg white nanogels (DEWN). After partial hydrolysis (ranging from 2.27% to 4.22%), the foaming capability (FC) of the mixture could reach more than 200%, much higher than that of unhydrolyzed DEWN (about 30%). After separated examination, such improve FC was dominantly attributed to the supernatant, which also impacted enhanced foaming stability (FS). The adsorption of the supernatant and the resulting surface rheological measurements exhibited that the extension of the hydrolysis time can increase the diffusion and adsorption rate to the interface, performing high elasticity. Specially, the Lissajous curves displayed that the samples with short enzymolysis time first appeared asymmetric shape, indicating that extending enzymolysis time could improve the elasticity of the interface, which contributed to the improvement in foaming properties. As in a wide range of pH values, the FC and FS of the supernatant performed well, especially exhibited excellent FS at pH 5.0. In general, pepsin hydrolysis treatment, as an oversimplified and green modification strategy could significantly improve the foaming performance of DEWN, and solve the problem of loss in its foamability of salted duck egg whites obtained after desalination treatment. Graphical abstract: Image 1 Highlights: Solid-state desalination method is an efficient and simple method for desalting salted egg whites. Pepsin hydrolysates of desalted egg white microgels exhibited excellent foamability and foam stability. The interfacial behavior was analyzed by combining nonlinear interface expansion rheology and Lissajous curve.